2023
DOI: 10.3389/fendo.2023.1080908
|View full text |Cite
|
Sign up to set email alerts
|

The use of modified TI-RADS using contrast-enhanced ultrasound features for classification purposes in the differential diagnosis of benign and malignant thyroid nodules: A prospective and multi-center study

Abstract: ObjectivesTo evaluate the diagnostic efficacy of a modified thyroid imaging reporting and data system (TI-RADS) in combination with contrast-enhanced ultrasound (CEUS) for differentiating between benign and malignant thyroid nodules and to assess inter-observer concordance between different observers.MethodsThis study included 3353 patients who underwent thyroid ultrasound (US) and CEUS in ten multi-centers between September 2018 and March 2020. Based on a modified TI-RADS classification using the CEUS enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…From table [5] and using equations, the sensitivity of ultrasound and FNAC for diagnosis of malignant thyroid nodules were 57.1% and 87.5% respectively. However, both were 100% specific for detection of malignant nodules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From table [5] and using equations, the sensitivity of ultrasound and FNAC for diagnosis of malignant thyroid nodules were 57.1% and 87.5% respectively. However, both were 100% specific for detection of malignant nodules.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the thyroid gland and assessment of thyroid nodules were conducted using the TIRADS, categorizing lesions into six classifications. Abdominal examinations included inspection and superficial palpation [5] .…”
Section: Methodsmentioning
confidence: 99%
“…For example, some Hashimoto’s nodules may show hypoechogenicity with blurred margins on 2D-US, which may be classified as TIRADS >4 and require unnecessary FNA according to the guidelines ( 7 , 40 , 41 ). CEUS, as a novel noninvasive microangiography technology, can reveal microvasculature with a smaller diameter (>40 µm) than that by CDFI (>100 µm) and is helpful in the detection of malignant thyroid nodules ( 42 , 43 ). Recent studies have indicated that CEUS could modify the current TIRADS to create a new risk stratification that may reduce unnecessary biopsies ( 42 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…CEUS, as a novel noninvasive microangiography technology, can reveal microvasculature with a smaller diameter (>40 µm) than that by CDFI (>100 µm) and is helpful in the detection of malignant thyroid nodules (42,43). Recent studies have indicated that CEUS could modify the current TIRADS to create a new risk stratification that may reduce unnecessary biopsies (42)(43)(44)(45)(46). Our team had published one CEUS-TIRADS model to differentiate thyroid nodules (C-TIRADS 4) by combining CEUS with C-TIRADS (46), which had high clinical practicability in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…There were other proposals of CEUS + TIRADS approach, with slightly different designs but also with improved outcomes One study found that when used together in a predictive model, TIRADS and CEUS they performed better than either method alone (P <0.05), with an accuracy of 86.6% for the combined score ( 21 ). In another multicentric study on a large number of cases, the authors found au AUC for the modified TIRADS of 0.936, sensitivity 93.6%, specificity 88.5%, with Kappa for CEUS evaluation of 0.81, describing good interobserver variability ( 34 ). In our group, for the B-mode-only TIRADS, the percentage of cancers identified in score 3 is 17.28%, in score 4 it is 57.9% and 81.25% in score 5; for the TIRADS + CEUS, in score 3 we identified 1.9% cancers, in score 4 we identified 23.6% and in score 5 – 68%.…”
Section: Discussionmentioning
confidence: 99%